Defining delirium in idiopathic Parkinson's disease: A systematic review. (July 2019) - Lawson, Rachael A.; McDonald, Claire; Burn, David J.
Abstract: Background: Parkinson's disease patients may be at increased risk of delirium and developing adverse outcomes, such as cognitive decline and increased mortality. Delirium is an acute state of confusion that has overlapping symptoms with Parkinson's dementia, making it difficult to identify. This study aimed to determine the diagnostic criteria, prevalence, management strategies and outcomes of delirium in Parkinson's through a systematic review of the literature. Methods: Seven databases were used to identify all articles published before February 2017 comprising two key terms: "Parkinson's Disease" and "delirium". Data were extracted from studies meeting predefined inclusion criteria. Results: Twenty articles were identified. Delirium prevalence in Parkinson's ranged from 0.3 to 60% depending on setting; a diagnosis of Parkinson's was associated with an increased risk of developing delirium. Delirium was identified/diagnosed using seven different criteria. Delirium may be associated with an increased length of hospital stay and worsening motor symptoms. We did not identify any studies examining the management of delirium in Parkinson's. Discussion: This review highlights the paucity of well-designed, appropriately powered studies investigating delirium in Parkinson's. The results suggest that delirium is a significant issue in people with Parkinson's and that having delirium may be a risk factor for adverse outcomes, particularly in inpatient settings. Further prospective research is needed to accurately determine the prevalence of delirium in Parkinson's, its management strategies and outcomes, and to evaluate diagnostic criteria to differentiate between the overlapping symptoms of Parkinson's and delirium. Highlights: Delirium prevalence in Parkinson's ranged from 0.3 to 60% depending on setting. Parkinson's was associated with an increased risk of developing delirium. Delirium may be a risk factor for adverse outcomes in Parkinson's. There was a paucity of well-designed, appropriately powered studies.